2020
DOI: 10.1002/hyp.13671
|View full text |Cite
|
Sign up to set email alerts
|

Amounts, forms, and management of nitrogen and phosphorus export from agricultural peatlands

Abstract: Peatlands provide a setting that is well suited for cranberry agriculture in the Northeastern United States. However, misconceptions exist about the amounts and forms of nitrogen (N) and phosphorus (P) export from cranberry farms. In this study, we report inorganic and organic forms of N and P export from five peatlands cultivated for cranberry production in southeastern, Massachusetts, United States. We then compare N loading rates among cranberry farms in southeastern Massachusetts, row crop farms in the Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Kennedy et al. (2016) reported that frost cycling could result in 35% water use reduction relative to conventional sprinkler irrigation on a frost night. This is a significant water saving as it results in a multiplier effect on chemical leaching reduction, energy use reduction, and labor cost savings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kennedy et al. (2016) reported that frost cycling could result in 35% water use reduction relative to conventional sprinkler irrigation on a frost night. This is a significant water saving as it results in a multiplier effect on chemical leaching reduction, energy use reduction, and labor cost savings.…”
Section: Resultsmentioning
confidence: 99%
“…Water management is a key component of sustainable intensification of cranberry production in Massachusetts. Previous research has shown that water management directly affects (a) crop yield (Caron et al., 2016), (b) environmental effects (Kennedy et al., 2020), (c) production costs (Olszewski et al., 2017), and (d) regulatory scrutiny (Mattson et al., 2015). One challenge facing Massachusetts growers is that soil moisture conditions are generally too wet to achieve optimal crop production (Lampinen & DeMoranville, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…x in N inputs of fertilizer (x = fert), floodwater (x = f), irrigation (x = i), surface water (x = sw-in), net groundwater (x = gw-net), and atmospheric deposition (x = atm) that is not retained at the surface (y = s) or in the vadose zone (y = vz) of the farm. This N transmission coefficient equals one minus the attenuation rate in other studies and was previously referred to as the nitrogen loss coefficient in Kennedy et al (2020). The net N export from the cranberry farm is calculated as the difference between N outputs and the fraction of N inputs that leaves the farm:…”
Section: Measuring Nitrogen Exportmentioning
confidence: 99%
“…Once Q net is known, the average N concentration in groundwater is applied to calculate F gw-net (Neill et al 2017, Kennedy et al 2018. Kennedy et al (2020) empirically calculated N transmission coefficients (c s f c vz f = 0.65, c s i c vz i = 0.78).…”
Section: Measuring Nitrogen Exportmentioning
confidence: 99%
See 1 more Smart Citation